Optimizing the xWORM assay for monitoring hookworm larvae motility - Lennox-Bulow, Danica; Becker, Luke; Loukas, Alex; Seymour, Jamie; Smout, Michael (Frontiers in Parasitology, 2023)
Parasitic worms (helminths) infect almost all taxa across the animal kingdom, and pose significant challenges to public health and economies, particularly in developing countries. To address this problem, researchers have developed various tools to measure the motility and viability of helminths. However, the conditions used in anthelmintic screening assays are often not optimised, and they can vary considerably between research teams. These unoptimized conditions can impact new drug screens as little is known about the effect of different conditions on the health of the target parasites. To improve future research this study determined the effect of key assay parameters such as media type, media concentration, in-well parasite density, and assay duration on the infective third-stage larva (L3) of two types of hookworms, Nippostrongylus brasiliensis in rodents and Necator americanus in humans. Conditions were screened over several days using the xWORM assay, a real time impedance-based helminth motility assay using the xCELLigence system with 96-well microplates. While results varied depending on the species and media used, the study found that 500-1000 L3/200µL well volume and a media concentration of 3.13 – 25% generally produced good to excellent assay conditions. This study’s findings can guide future selection of xWORM assay parameters for novel drug trials involving these parasite species and serve as a suggested model for optimising trial conditions for alternate parasite targets and assays.